The Collapse of the Weimar Republic : Political Economy and Crisis - Abraham, David, (Historical Materialism Book Series ;, 2025)
What enables a liberal democracy to survive in a capitalist society? How did Weimar Germany, one of the first modern welfare states, balance the interests of working people and economic elites? What leads elites to undermine democracy, and what happens when they do? Theoretically sophisticated within a Marxist tradition and deeply researched in both public and private archives, The Collapse of the Weimar Republic analyzes the complex political economy of inter-war Germany and examines why and how Germany's economic and political leaders turned away from social democracy and international integration, instead turning to the Nazi party to preserve their dominance.